Complex Systems Design & Management Asia Smart Transportation: Proceedings of the Third Asia-Pacific Conference on Complex Systems Design & Management, CSD&M Asia 2018 - Cardin, Michel Alexandre; Hastings, Daniel; Jackson, Peter; Krob, Daniel; Lui, Pao Chuen; Schmitt, Gerhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers all papers presented at the third edition of the international conference "Complex Systems Design & Management Asia" (CSD&M Asia 2018), which was held at the National University of Singapore (NUS) on December 6-7, 2018. Mastering complex systems requires an integrated understanding of industrial practices as well as sophisticated theoretical techniques and tools. This vision was the inspiration for creating an annual forum in the Asia-Pacific region dedicated to bringing together academic researchers & industrial actors working on architecture, modeling & engineering of complex technical & organizational systems. These proceedings cover the latest trends in the emerging field of complex systems, both from an academic and a professional perspective. Special emphasis is placed on "Smart Transportation." The CSD&M Asia 2018 conference is organized under the guidance of CESAM Community which is managed by the non-profit organization CESAMES. The goal ofCESAM Community is to structure the sharing of good practices in enterprise and systems architecture, and to certify the level of knowledge and proficiency in this field by means of CESAM certification.
A Net-based Formal Framework for Causal Loop Diagrams -- Modeling Operations of a Custom Hiring Center Using Agent Based Modeling and Discrete Event Simulation -- Modelling the Eﬃcacy of Assurance Strategies for Better Integration, Interoperability and Information Assurance in Family-of-System-of-Systems Portfolios -- Multi-class Fleet Sizing and Mobility-on-Demand Service -- SMACOF Hierarchical Clustering to Manage Complex Design Problems with the Design Structure Matrix -- Modelling Safe and Secure Cooperative Intelligent Transport Systems -- Detection of Teamwork Behavior as Meaningful Exploration of Tradespace during Project Design -- Leveraging Data Analytics in Systems Engineering - Towards A Quantum Leap in Railway Reliability.
Keywords: Dynamics; Nonlinear theories; Computational intelligence; Applied Dynamical Systems; Computational Intelligence